Birth weight discordance, gene expression, and DNA methylation: A scoping review of epigenetic twin studies - Dany Laure Wadji; Zsofia Nemoda; Chantal Martin-Soelch; Linda Booij; Chantal Wicky (PLoS ONE, 2025)
Background Birth weight is considered as an important indicator of environmental conditions during prenatal development. Molecular mechanisms, including epigenetic modifications, play central roles in the body’s adaptation to ever-changing environmental conditions. Twin study designs offer a powerful approach for distinguishing environmental from genetic effects. Specifically, within-pair comparisons of monozygotic twins can be used to differentiate unique individual environmental factors from shared environmental and genetic contributions. Notably, numerous studies in monozygotic twins have shown associations between prenatal environment and birth weight discordance (BWD), and suggested a potential involvement of gene expression and epigenetic factors mediating the association. Objective To conduct a scoping review of the literature on definitions of BWD and on epigenetic modifications and gene expression changes associated with BWD in twins. Method Following PRISMA guidelines, we searched PubMed and Ovid MEDLINE(R) databases and included 34 twin studies focusing on birth weight and epigenetic or gene expression outcomes. Results There is a lack of consensus on BWD values when comparing groups of twins for their risks of perinatal mortality and morbidity, which vary between 15–30% depending on the type of placentation and gestational age. The gene expression twin studies measured mostly metabolism-related candidate genes in placental tissues. Only small-scale twin studies measured BWD associated with gene expression patterns on genome-wide level using neonatal cells. Most DNA methylation twin studies conducted epigenome-level analyses, and studies differ substantially in terms of tissue type and age of the children. Differences in DNA methylation patterns measured in blood or saliva samples of the twins later in life were mostly in genes related to signal transduction, cell differentiation and proliferation processes. Conclusion Transcriptional changes of placental glucose transporters and hypoxia-induced proteins possibly reflect compensatory processes in twin pregnancies. Gene ontology analysis of the differentially methylated genes associated with BWD pointed to transcription regulation and tissue development.